Demographic and pathogens of domestic, free-roaming pets and the implications for wild carnivores and human health in the San Luis Region of Costa Rica - Conrad, Joseph (2021)
Habitat loss and degradation, restricted ranges, prey exploitation, and poaching are important factors for the decline of several wild carnivore populations and additional stress from infectious agents is an increasing concern. Given the rapid growth of human populations in some regions like Costa Rica, pathogens introduced, sustained, and transmitted by domestic carnivores may be particularly important. To better understand the significance of domestic carnivore pathogens for wildlife, we determine the prevalence of infection and possible mechanisms for contact between the two groups. The demographics, role in the household, and pathogens of pet dogs and cats was studied during three annual spay/neuter clinics in San Luis, Costa Rica. Most dogs were owned primarily as pets and guard animals, but ~10% were used for hunting. Cats were owned primarily as pets and for pest control. Both roamed freely outdoors. We detected high prevalences of some pathogens (e.g., carnivore protoparvovirus 1 and Toxoplasma gondii). Some pathogens are known to persist in the environment, which increases the probability of exposure to wild carnivores. This study demonstrated that domestic pets in San Luis, home to a number of protected and endangered wildlife species, are infected with pathogens to which these wild species are potentially susceptible. Additionally, results from our questionnaire support the potential for domestic and wild animal contact, which may result in disease spillover.